Phase Lag Analyses on Ictal Scalp Electroencephalography May Predict Outcomes of Corpus Callosotomy for Epileptic Spasms - Oguri, Masayoshi; Okanishi, Tohru; Kanai, Sotaro; Baba, Shimpei; Nishimura, Mitsuyo; Ogo, Kaoru; Himoto, Takashi; Okanari, Kazuo; Maegaki, Yoshihiro; Enoki, Hideo; Fujimoto, Ayataka (Frontiers in Neurology, 2020)
Objective: We aimed to clarify the patterns of ictal power and phase lag among bilateral hemispheres on scalp electroencephalography (EEG) recorded preoperatively during epileptic spasms (ES), and the correlation with the outcomes following corpus callosotomy. Methods: We enrolled 17 patients who underwent corpus callosotomy for ES before 20 years of age. After corpus callosotomy, seven patients did not experience further ES (favorable outcome group), and the remaining 10 patients had ongoing ES (unfavorable outcome group). We used preoperative scalp EEG data from monopolar montages using the average reference. The relative power spectrum (PS), ictal power laterality (IPL) among the hemispheres, and phase lag, calculated by the cross-power spectrum (CPS) among symmetrical electrodes (i.e., F3 and F4), were analyzed in the EEG data of ES from 143 preoperative scalp video-EEG records. Analyses were conducted separately in each frequency band from the delta, theta, alpha, beta, and gamma range. We compared the means of those data in each patient between favorable and unfavorable outcome groups. Results: Among all frequency bands, no significant differences were seen in the individual mean relative PSs in the favorable and unfavorable outcome group. Although the mean IPLs in each patient tended to be high in the unfavorable outcome group, no significant differences were found. The mean CPSs in the delta, theta, and gamma frequency bands were significantly higher in the unfavorable than in the favorable outcome group. Using Youden index, the optimal cut-off points of those mean CPS values for unfavorable outcomes were 64.00 in delta band (sensitivity: 100%, specificity: 80%), 74.20 in theta band (100%, 80%), and 82.05 in gamma band (100%, 80%). Subanalyses indicated that those CPS differences originated from pairs of symmetrical electrodes in bilateral frontal and temporal areas. Significance: Ictal power and laterality of the ictal power in each frequency band were not associated with the outcomes of CC; however, the phase lags seen in delta, theta, and gamma frequency bands were larger in the unfavorable than in the favorable outcome group. The phase lags may predict outcomes of CC for ES on presurgical scalp-ictal EEGs.